Exploring Cross-linguistic Effects and Phonetic Interactions in the Context of Bilingualism - Amengual, Mark (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue includes fifteen original state-of-the-art research articles from leading scholars that examine cross-linguistic influence in bilingual speech. These experimental studies contribute to the growing number of studies on multilingual phonetics and phonology by introducing novel empirical data collection techniques, sophisticated methodologies, and acoustic analyses, while also presenting findings that provide robust theoretical implications to a variety of subfields, such as L2 acquisition, L3 acquisition, laboratory phonology, acoustic phonetics, psycholinguistics, sociophonetics, blingualism, and language contact. These studies in this book further elucidate the nature of phonetic interactions in the context of bilingualism and multilingualism and outline future directions in multilingual phonetics and phonology research.